Analisis Audit Operasional atas Persediaan Barang Consumable Studi Kasus pada PT. Pipa Mas Putih - Gus Muhammad Taufik; Indarti Indarti; Arini Arini (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
This study aims to determine the impact of the implementation of an operational audit of the inventory of goods at PT. Pipa Mas Putih Duri. The data analysis method used in this research is the descriptive qualitative research method. Based on the results of the research that has been analyzed based on interviews and direct observation of the object of the research, PT. Pipa Mas Putih has carried out an operational audit properly, as evidenced by the fulfillment of the stages of the operational audit stages. Furthermore, PT Pipa Mas Putih Duri already has several procedures regarding the management of goods inventory. Based on the checklist carried out, the operational audit and inventory management at PT. Pipa Mas Putih Duri are already running well.Keywords: Operational Audit, Management, Inventory